Nascidas do sol e da chuva: Minas Gerais e o combate às saúvas (1928-1936) - Valeria Mara da Silva (2007)
This dissertation has for objective to analyze the quarrels concerning the combat to the ants saúvas (Atta spp), in the period between 1928 e1936 in the State of Minas Gerais. The questions related to this insect-plague had been analyzed from the texts produced for professionals technician who works on agriculture, mainly agronomists. We search to identify how that the combat was seen for these professionals and how they translated the demands of the agriculturists and the society. Moreover, we analyze the used strategies to mobilize the men against the Atta and the paper of the public administration in the conduction of the Campanha Nacional against the saúva of 1935. In this direction, we look for to understand the some symbolic aspects around that he was considered one of the greatest wounds of national agriculture.